Axial compression mesoscale modelling of RC columns after reinforcement-electrochemical chloride extraction. (June 2021) - Li, Yue; Liu, Jianglin; Wang, Zigeng; Su, Yingqiu
Abstract: The reinforced concrete column after corrosion of chloride salt was subjected to magnesium phosphate cement (MPC)-carbon fiber reinforced plastics (CFRP) reinforcement and electrochemical chloride extraction (ECE) integration experiment. The axial compression behavior of the reinforced concrete column was tested, and then the numerical analysis was carried out. Two types of the corroded reinforced concrete columns were prepared for the test. The columns in type 1 were naturally corroded, and the columns in type 2 were electrified to accelerate the corrosion until the theoretical mass corrosion rate of steel bars reached 15%. Afterward, the MPC-CFRP was used to strengthen the corroded reinforced concrete columns and to remove the inside chlorine by electrochemistry method. The test results showed that the ultimate compressive capacity of the reinforced concrete columns strengthened by the MPC-CFRP increased by more than 22.63%. However, after ECE (current density, 3 A/m 2 ), the ultimate compressive capacity of the reinforced concrete columns strengthened by MPC-CFRP reduced by 3.07% − 3.66%, and the chloride ion content at the interface between steel bar and concrete reduced by 78.52%, which postponed the corrosion of the steel bars. In addition, considering the complex nonlinear bond slip relationship between the steel bar and the concrete interface, a 3D mesoscopic finite element plastic damage model of the reinforced concrete columns strengthened by the MPC-CFRP was established. The numerical results were in good agreement with the test results, which indicated the 3D mesoscopic finite element numerical model can predict the compressive behavior of the reinforced concrete columns adequately.